Psihopoetika of Chingiz Aitmatov (Eurasian Journal of Philology Science and Education, 2016)
The article focuses on the issue of psihopoetiki Chingiz Aitmatov. The material for analysis was the novel «Jamila» of Aitmatov. Features inherent psihopoetika writer clearly expressed in the novel «Jamila». Examined the relationship, the relationship and the contradiction of human phenomena, both spiritual and physical, domestic and foreign, their artistic features in the structure of psihopoetiks of the writer. Substantiates the idea that psihopoetika Aitmatov – it is an example of creative thinking, creative writing high.
Keywords: Chingiz Aitmatov; psihopoetika; soul and body; inner and outer; synthetic and analytical; epic and lyrical; the relationship mastery.